FRICTION STIR PROCESSING OF Al-SiC COMPOSITE FOR SUPER PLASTIC FORMING - G. Venkatesh Kumar , Ms.Catherin victoria , Raghvan K V, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Friction stir processing (FSP) is one of the new and thermo mechanical processing techniques that alters the micro structural and mechanical properties of the material in single pass to achieve maximum performance with low production cost in less time using a simple and inexpensive tool. Friction stir processing can reduce the grain size conferring excellent super plastic behavior in aluminium alloys. The important aspects of the friction stir processing tool is material selection, Tool Geometry, Load bearing ability, mechanisms of tool degradation and process economics. Preliminary studies of different FS processed alloys report the processed zone to contain fine grained, homogeneous and equiaxed microstructure. In the present work, sheets of aluminum alloys were friction stir processed under various combinations of rotational and translational speeds. The processing forces were measured during the process and the resulting microstructure was analyzed. The grain refinement was observed to vary directly with rotational speed and inversely with the translational speed